Publications, 1979, by or with the assistance of Wildfowl Trust staff and facilities - anonymous, Anonymous (Wildfowl, 1980)
Atkinson-Willes, G. L. Vogelaars in 57 landen teiden hun Watervogels. De Lepelaar 65: 24-27. Butler, P. J. The use of radio telemetry in the studies of diving and flying in birds. Pp. 569-77 in Almaner, C. J. & MacDonald, D. W. (eds.) A Handbook on Biotelemetry and Radio Tracking. London: Pergamon. Coleman, A. E. & Minton, C. D. T. Pairing and breeding of mute Swans in relation to natal area. Wildfowl 30: 27-30. Evans, M. E. Aspects of the life style of the Bewick’s Swan, based on recognition of individuals at a wintering site. Bird Study 26: 149-62. Evans, M. E. The effects of weather on the wintering of Bewick’s Swans at Slimbridge, England. Ornis Scand. 10: 124-32. Ferns, P. N ., MacAlpine-Leny, I. H. & G oss-Custard, J. D. Telemetary of heart rate as a possible method of estimating energy expenditure in the Redshank, Tringa totanus. Pp. 595-601 in Almaner, C. J. & M acDonald, D. W. (eds.) A H andbook on Biotelemetry and Radio Tracking. London: Pergamon. Forshaw, D. Pinkfoot numbers in Lancashire. W A G B I Mag. Autum n 1979: 16-19. Hillgarth, N. & Kear, J. Diseases of seaduck in captivity. Wildfowl 30: 135-41. Hillgarth, N. & K ear, J. Diseases of sheldgeese and shelducks in captivity. W ildfowl 30: 142-46. Kear, J. Wildfowl at risk, 1979. Wildfowl 30: 159-61. Lessells, C. M ., Sibly, R. M ., Owen, M. & Ellis, S. Weights of female Barnacle Geese during breeding. Wildfowl 30: 72-74. Matthews, G. V. T. All over Europe/G ibier sans frontieres. Naturopa 32: 14-18. Matthews, G. V. T. Impact on the natural environm ent. Pp. 3 in Seminar on emergency arrangements for combatting oil pollution (Seacop). Ogilvie, M. A. The Birdwatcher’s Guide to British Wetlands. London: Batsford. Ogilvie, M. A. General introduction to Branta b. bernicla with particular reference to the wintering areas. Proc. Tech. Mtg. Waterfowl Manag. Paris 1977: 10-18. Ogilvie, M. A . & Sharrock, J. T. R. In Focus. Binoculars and telescopes. Birds 7: 17-19. Owen, M. & King, R. The duration of the flightless period in free-living Mallard. Bird Study 27: 267-9. Owen, M. & Ogilvie, M. A . Moult, weight and measurements of Barnacle Geese in Spitsbergen. Condor 81: 42-52. Owen, M. & Wells, R. Territorial behaviour in breeding geese—a re-examination of Ryder’s hypothesis. Wildfowl 30: 20-26. St Joseph, A . K. M. An assessment of population levels of Branta b. bernicla in south-eastern England. Proc. Tech. Mtg. Waterfowl Manag. Paris 1977: 132-37. St Joseph, A. K. M. The seasonal distribution and movements of Branta b. bernicla in western Europe. Proc. Tech. Mtg. Waterfowl Manag. Paris 1977: 45-59. Seegar, W. S. Prevalence of parasitic heartworm s in swans in England. Wildfowl 30: 147-50. Smart, M. (E d.) Liquid Assets. Slimbridge: I.W .R .B . Smart. M. Wat is en doet het ‘International Waterfowl Research Bureau'. De Lepelaar 64: 30-2. Stanley, P. I. & St Joseph, A. K. M. Poisoning of D ark-bellied Brent Geese in Essex, February 1979. Wildfowl 30: 154. Tanner, M. F. Wildfowl, reservoirs and recreation. W SA C Res. Rep. 5. 40 pp. Tubbs, C. R. Wildfowl and waders in Langstone Harbour. Brit. Birds 70: 177-99. Tuite, C. H. The use of radio tracking in an ecological study on the Lesser Flamingo in the Eastern Rift Valley. Pp. 729-32 in Almaner, C. J. & MacD onald, D. W. (eds.) A Handbook on Biotelemetry and Radio Tracking. London: Pergamon.